Use of GIS in Road Infrastructure Development and Management (International Journal of Innovative Research in Engineering & Management, 2022)
GIS Architecture is an essential tool to be  placed on comprehending the information of spatial and non spatial data over a space and time. Rural Road Network  comprises of group of nodes and links. The Network Configuration is a combination of these links with a  directional orientation to the nodes which are the Centre  heads of the habitations spread over the space. As most of the  features are static in nature there is a need to Geo-Reference  permanently and the dynamic interactions in terms of  planning, construction, maintenance can be visualized over a  time on this spatial frame. To create the rural asset, GIS is a  great supportive tool which connects advance technologies  and the conventional practices on a common platform. There  is a need to decide the type of architecture which matches to  the rural asset creation for display, reciprocate interactions,  updating, data schema attachment and interfacing with  advanced technologies.
Keywords: GIS; Road Infrastructure; CGIS; Technology; Geographic